Predictive Markers for the Efficacy of Anti–PD‐1/PD‐L1 Antibodies in Lung Cancer. Issue 7 (July 2016) - Shukuya, Takehito; Carbone, David P.
ABSTRACT : N/A: Blockade of the programmed death protein 1 (PD‐1)/programmed death ligand 1 (PD‐L1) axis using antibodies against the associated receptors and ligands has yielded good clinical responses and improved overall survival in patients with non–small cell lung cancer (NSCLC). Once patients show a response to anti–PD‐1/PD‐L1 antibody, the median duration of response is often longer than that achieved using existing cytotoxic agents and even some molecular targeted agents. However, the response rates to these antibodies are only 15% to 20% in unselected patients with NSCLC and the cost of this therapy is high. Therefore, there is an urgent need for effective predictive biomarkers to identify patients likely to benefit. PD‐L1 expression, which can be detected by immunohistochemical analysis, is a rational biomarker for selecting responders to anti–PD‐1/PD‐L1 antibody treatments, and this selection method has been introduced into clinical practice. However, the response rate to anti–PD‐1/PD‐L1 antibody in PD‐L1–expressing patients with NSCLC is only 15% to 45%, response can occur in PD‐L1–negative patients, and predictability based on PD‐L1 expression may differ between nonsquamous NSCLC and squamous cell NSCLC. In addition, the methods of immunohistochemical analysis and evaluation of its results differ for different anti–PD‐1/PD‐L1 agents. This article reviews the existing data on predictive markers for the efficacy of anti–PD‐1/PD‐L1 antibodies in NSCLC.